Pola Komunikasi Keluarga untuk Ketahanan Ibu Hadapi Stunting Anak di Kelurahan Pisangan Jaya, Kabupaten Tangerang - Ade Rahmah; Asriyani Sagiyanto; Alifia Khoerina Kusditia; Ardian Setio Utomo; Elisa Triwiyatsih (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2026)
Stunting is a public health problem with long-term impacts on children's physical and cognitive development. In Pisangan Jaya Village, Tangerang Regency, the prevalence of stunting remained at 7.3% in 2025. The Tangerang Regency Government has set a target to reduce stunting prevalence to a maximum of 14%, in line with the national target, while the current rate has already declined to around 7%. This issue raises the question of how family communication patterns contribute to maternal resilience in addressing child stunting. This study aims to analyze family communication patterns that can enhance maternal psychological resilience in preventing and managing stunting. The study employs a descriptive qualitative approach using both primary and secondary data. Informants consisted of mothers with children at risk of stunting, their husbands, and Posyandu cadres. The findings indicate that open and empathy-based family communication patterns can strengthen maternal resilience by helping mothers manage stress, understand the importance of child nutrition, and make appropriate parenting decisions. In contrast, closed and authoritarian communication patterns tend to weaken maternal adaptability. In conclusion, family communication patterns are a key factor in enhancing maternal resilience, which in turn has implications for the success of stunting prevention and management at the family level. Therefore, strengthening family communication should become an integral part of community-based stunting intervention strategies.